Respuesta :

Answer:

1/13

Step-by-step explanation:

√ 1/196 = (1/196)*(1/2)

= (1)*(1/2)/(13)^(2×1/2)

=1/13

Your Answer is 1/14

PLZ MARK ME BRANLIEST

Step-by-step explanation:

Apply the square root to each part:

sqrt(1) = sqrt(1^2) = 1

sqrt(196) = sqrt(14^2) = 14

The general rule is sqrt(x^2) = x where x is any positive number.

Note how

(1/14)*(1/14) = (1*1)/(14*14) = 1/196

showing that 1/14 multiplied with itself is 1/196. The square root just thinks of this process in reverse. You start with 1/196 and end up with 1/14.